Importance of Sanskrit Language in Natural Language Processing and Machine Translation: a Review - Vaishali Kherdekar (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This paper presents an importance of the Sanskrit language in Computer Science and Information Technology i.e. how the Sanskrit language plays a key role in the research area. This paper also presents how the Sanskrit language is important in various fields of computer science such as natural language processing, automatic speech recognition, machine translation, etc. It is also beneficial for human health. In Sanskrit, sentences can be formed using a minimum number of words than in any other language. In this paper reasons for selecting Sanskrit as a Natural Language Processing are presented. This paper also presents the importance of the Sanskrit language in research.